Slow recovery of microclimate temperature buffering capacity after clear-cuts in boreal forests - Starck, Iris; Aalto, Juha; Hancock, Steven; Valkonen, Sauli; Kalliovirta, Leena; Maeda, Eduardo (Agricultural and Forest Meteorology)
The majority of Fennoscandian boreal forests are managed. Forest management inherently changes the physical structure of forests, thus altering ecosystem functions and the conditions for living organisms within these environments. However, the impacts of management on the microclimate buffering of boreal forests have not been comprehensively studied, despite that microclimate is one of the key determinants of biodiversity. Here, we studied the effect of forest structure and management on the temperature buffering capacity of boreal forests using terrestrial laser scanning and microclimate measurements. We measured the temperature variability on forest plots representing two management types: even-aged rotation forestry and uneven-aged forestry. To quantify buffering, we calculated the slope coefficient of the linear regression between microclimate and clear-cut temperatures. We found that the total amount of plant material alone was not an adequate predictor of the buffering. Instead, increasing canopy layers and the density of the understory led to more buffered temperature variability compared to clear-cuts and forests with fewer layers. The buffering was high in both mature even-aged and uneven-aged sites, but the effect in even-aged forests depended on stand age, suggesting that a strong buffering capacity could be reached only after approximately 30 years after clear-cut. In uneven-aged stands, the buffering capacity varied with recurring partial selection cuttings, but never lead to a full coupling with open-air temperatures like in even-aged stands after clear-cuts. We conclude that despite the buffering being on average stronger in mature even-aged stands than in uneven-aged stands, it can take decades for a clear-cut stand to reach the same buffering capacity as an uneven-aged forest with continuous tree cover, and it will eventually disappear after a new clear-cut harvest. From biodiversity perspective, uneven-aged management can create more temporally stable microclimatic conditions and can thus aid ...